(untitled) (International Journal of Engineering and Computer Science, 2014)
In the digital image processing copyright protection and authentication have become more significant, in order to achieve this digital different watermarking techniques are introduced for the security. We propose an algorithm in wavelet domain using wavelet transformation for a digital invisible watermarking is to embedded into a QR code image. In our method we embed a binary image logo considered as watermark embedded into one of selected wavelet subband. The experimental results show that our method has more robustness to attacks in different considerations and it can achieve a viable copyright protection and authentication.